2022
DOI: 10.3389/fnmol.2022.982202
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of keratinocytes in nociceptive transduction and regulation

Abstract: Keratinocytes are the predominant block-building cells in the epidermis. Emerging evidence has elucidated the roles of keratinocytes in a wide range of pathophysiological processes including cutaneous nociception, pruritus, and inflammation. Intraepidermal free nerve endings are entirely enwrapped within the gutters of keratinocyte cytoplasm and form en passant synaptic-like contacts with keratinocytes. Keratinocytes can detect thermal, mechanical, and chemical stimuli through transient receptor potential ion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 190 publications
0
10
0
Order By: Relevance
“…17,81,96 The receptors for these neuromediators are expressed by a variety of native skin cells as well as immune cells. 53 Various events taking place during physiologic and pathologic cutaneous states provide hints of close functional relationship between CSANs and CICs. Native skin cells including KCs and endothelial cells and immune cells chiefly mast cells routinely release neuromediators under physiological circumstances but the effects are subtle.…”
Section: Current E Viden Ce Favouring Cine Cross Talkmentioning
confidence: 99%
See 2 more Smart Citations
“…17,81,96 The receptors for these neuromediators are expressed by a variety of native skin cells as well as immune cells. 53 Various events taking place during physiologic and pathologic cutaneous states provide hints of close functional relationship between CSANs and CICs. Native skin cells including KCs and endothelial cells and immune cells chiefly mast cells routinely release neuromediators under physiological circumstances but the effects are subtle.…”
Section: Current E Viden Ce Favouring Cine Cross Talkmentioning
confidence: 99%
“…Once stimulated, CSANs release more neuromediators that further activate more nerve fibres by recruiting inflammatory cells 17,81,96 . The receptors for these neuromediators are expressed by a variety of native skin cells as well as immune cells 53 …”
Section: Current Evidence Favouring Cine Crosstalkmentioning
confidence: 99%
See 1 more Smart Citation
“… 59 Early in the disease, the release of various endogenous substances can affect TRP pathway function, leading to infection and disease progression (for example, the release of leukotriene B4 induces TRPV1 activation). 60 One of the most critical pathological processes is the development of cancer cells. More and more evidence has shown that changes in TRP channel expression levels play a crucial role in the occurrence and development of tumors, including proliferation, 61 migration, 62 invasion, 63 and other characteristics of glioma.…”
Section: The Trp Superfamilymentioning
confidence: 99%
“…The skin serves as the body's primary interface with the external environment and plays a pivotal role in defense and sensory perception. Keratinocytes are the predominant cell type within the epidermis and make a significant contribution to peripheral pain sensitization [12]. Using a chronic post-ischemia pain (CPIP) model to mimic CRPS in male rats, our team previously identified the involvement of keratinocytes and N-methyl-D-asparagic acid (NMDA) receptor subunit 2 B (NR2B) in both the peripheral and central sensitization of CRPS [13].…”
Section: Introductionmentioning
confidence: 99%